Numerical Analysis and Verification of Residual Stress in T Joint of S355 Steel (Fracture and Structural Integrity, 2020)
T joint is a widely used welding form. The welding deformation and residual stress produced during the welding process will affect the integrity and reliability of the structure. In this study, S355 low alloy steel was used as test material, and the thermal-mechanical coupling characteristics of multi-layer welding were combined with SYSWELD finite element software to calculate the residual stress of T joint after welding. The residual stress of multi-layer welding T joint with tangent tube and sheet after welding was measured by X-ray diffraction method. The results showed that the numerical simulation agreed well with the experimental results. For the transverse residual stress, the maximum residual stress appeared near the weld toe, and the transverse stress perpendicular to the weld direction presented tensile stress at the weld center and presented stress at the tube surface far from the weld. For the longitudinal residual stress, the maximum residual stress also appeared near the weld toe, and the value was the largest at the center of the weld and decreased along the direction perpendicular to the weld. The research results can provide a reference for actual welding design.
Keywords: T joint; Residual stress; Welding deformation; Finite element method